Remote genetic counselling provision for heart failure patients at a UK transplant centre. (2nd July 2022) - Quinn, E M; Mason, S; Halliday, B
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiomyopathy has been highlighted as one of the key drivers of heart failure, particularly dilated cardiomyopathy (DCM) (5, 1). Finding the correct diagnosis for patients is not only important to their health, but to that of their family members (2). European guidelines recommend genetic counselling and testing for all patients with a cardiomyopathy diagnosis (3). Genetic counselling involves communicating complex information and providing support to patients and families with inherited conditions. It is recommended that patients undergo genetic counselling alongside genetic testing (6). Purpose: historically, the heart failure team had no formal pathway in place for genetic testing. We set to establish a remote provision for genetic counselling and testing. We hoped to increase access to genetic services, without additional trips to the hospital in this already burdened patient group. Methods: A genetic counsellor (GC) attended the weekly team meeting to raise awareness of the genetic service and help identify eligible patients. Eligibility was determined using criteria from the national genomic test directory (4). Eligible patients had appointments via video or phone call. Outpatients who consented to genetic testing had blood samples arranged locally or at an upcoming hospital appointment. Inpatients had blood samples taken during their hospital stay. Forty-one eligible patients were identified, the majority had DCM (n=40) and one had arrhythmogenic right ventricular cardiomyopathy (ARVC). Genetic testing was performed using a diagnostic DCM or ARVC panel. Results were classified as positive, i.e. pathogenic or likely pathogenic variant identified; negative, i.e. no pathogenic variant identified; or inconclusive, i.e. variant of unknown significance identified. Results were fed back to patients by virtual genetic counselling appointment. GCs facilitated screening of family members as appropriate. Results: In the period, July 2020 to January 2022, 41 patients attended virtual genetic counselling appointments and consented to genetic testing. Of these, 19 received a positive genetic result, 4 an inconclusive result, and 18 a negative result. The majority of positive results were identified in the TTN gene (n=9) (see Figure 1). To date, six family members have been identified as gene positive and requiring ongoing screening, whilst six have now been discharged on the basis of a gene negative result. These are preliminary figures and expected to grow as more family members are able to access genetic counselling Conclusion: Heart failure patients represent an underserved population who may benefit from genetic testing alongside genetic counselling. Remote genetic counselling is an effective service delivery model. A significant proportion of patients (46.3%) received a positive genetic result. This has potential benefits, not only to the patient but to family members.